Entwining : Revitalizing by weaving different entities together, Redevelopment of RDA market area, Rajshahi - Tasneem, Mayeesha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2020.